Anti-aging effect of glycerophosphocholine in Steinernema kraussei 0657L - Li, Xi-Tong; Qian, Xiu-Juan; Chen, Hong; Wang, Xing-Duo; Wu, Xia (Frontiers in Physiology, 2024)
Glycerophosphocholine (GPC) is a water-soluble small molecule found naturally in humans and foods such as milk and soybeans. It can activate the IIS pathway by regulating the expression of daf-2, ins-18 and daf-16 genes, sek-1 and skn-1 genes of MAPK pathway, sod-3, ctl-1, gst-4 and other antioxidant genes. GPC can relieve symptoms related to aging in organisms. The aim of this study was to probe the effects of GPC on the longevity and stress resistance of the entomopathogenic nematode (EPN) Steinernema kraussei 0657L strain. The results showed that the lifespan of S. kraussei 0657L was significantly prolonged by 50 mM GPC treatment, which was 54.55% longer than that of the control (0 mM GPC). GPC significantly inhibited reactive oxygen species (ROS) and lipofuscin accumulation, but the body size and fecundity of S. kraussei 0657L had little changed. At the same time, the longevity of S. kraussei 0657L exposed to heat shock and UV-B radiation was significantly prolonged than that with no external stress. GPC supplementation increased the activity of antioxidant enzymes and corresponding gene expression. Under treatment with 50 mM GPC, the activities of superoxide dismutase and catalase were increased by 1.90- and 4.13-fold, respectively, the expression of the sod-3 and ctl-1 genes was increased by 3.60- and 0.60-fold, respectively, and harmful reactive oxygen species were removed. In addition, the expression levels of the ins-18, skn-1, sek-1 and gst-4 genes related to the insulin/IGF-1 signaling pathway were upregulated 1.04-, 1.84-, 2.21- and 1.24-fold, respectively. These results indicate that GPC is mainly involved in the lifespan regulation of S. kraussei 0657L and plays an important role in resistance to external stress by activating the insulin/IGF-1 signaling pathway and downstream PI3K/MAPK kinase, creating a new idea for improving the commercial efficacy of S. kraussei. It also laid a theoretical foundation for its further efficient development and utilization in the field of biological control.